Does the Level of Reproductive Knowledge Specific to Inflammatory Bowel Disease Predict Childlessness among Women with Inflammatory Bowel Disease? - Vivian W Huang; Hsiu-Ju Chang; Karen I Kroeker; Karen J Goodman; Kathleen M Hegadoren; Levinus A Dieleman; Richard N Fedorak (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Women with inflammatory bowel disease (IBD) may choose to remain childless due to a lack of IBD-specific reproductive knowledge.